Relationships between trihalomethane formation potential and natural organic matter surrogates in raw water and coagulated water of shallow wells near a closed unsanitary solid waste dumping site - Vasuree Jiarsiriku (Chulalongkorn University, 2006)
Thesis (M.Sc.)--Chulalongkorn University, 2003